Volatile chemical component differences between fully and partially dried merbau (Intsia sp.) wood using gas chromatography-mass spectrometry (GC-MS) in Malaysia - Gina Francesca Gabriel; Nur Fatin Ghazali; Dheephikha Kumaraguru; Khairul Osman; Noor Hazfalinda Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Wood is one of the most common material found in homes and industrial fires, particularly in Malaysia. The abundance of different types of wood used to build structures, frames, furniture and others are important to take note as wood is a conducive material that can be used to initiate and propagate a fire, particularly in forensic fire cases. This study was conducted to provide the volatile chemical fingerprint of burnt Merbau (Intsia sp.) wood using gas chromatographymass spectrometry (GC-MS). The wood samples were prepared under two conditions; fully dried and partially dried. Six study replications of each condition were burnt outdoors and underwent an extraction process using activated carbon tablets. The tablets were incubated in an oven for 16 hours at 80ºC. Next, the tablets were desorbed in two different types of solvent; pentane and ethanol. The pentane- and ethanol-desorbed volatile products were then introduced into the GC-MS. Volatile organic compounds obtained across both conditions were in the range of volatile acids, aromatics and its derivatives, D-glucopyranose, phenolic derivatives and cycloalkane. The compounds emitted by fully and partially dried Merbau wood samples were similar, differing only in the absence of malonic acid and succinic acid in partially dried Merbau wood samples. Both solvents desorbed different types of volatile compounds. The burning behaviour of partially dried Merbau wood were different to those documented from fully dried Merbau wood and is attributed to the composition of wood rather than the dry or wet conditions.